Association between serum uric acid levels and cardiovascular disease in middle-aged and elderly Chinese individuals - Qin, Li (BioMed Central, 2014)
BACKGROUND: A link between uric acid (UA) levels and cardiovascular diseases has been previously reported. However, its importance as a risk factor is still controversial. This study sought to determine whether elevated serum uric acid levels are associated with cardiovascular disease (CVD) in middle-aged and elderly Chinese individuals. METHODS: We conducted a population-based cross-sectional study in Shanghai, with a total of 8510 participants aged ≥40 years. The CVD included diagnosed coronary heart disease (CHD) and stroke. MetS was defined according to the updated National Cholesterol Education Program Adult Treatment Panel III criteria for Asian Americans. RESULTS: Uric acid levels were positively associated with BMI, waist circumference, triglycerides, systolic blood pressure, diastolic blood pressure, glycohemoglobin, fasting plasma glucose, postprandial 2-hour plasma glucose (all P < 0.05), and negatively associated with HDL-cholesterol (P < 0.001). The prevalence of CVD significantly increased with increasing quartiles of UA in those without MetS group (p trend < 0.001), but not necessarily increased in those with MetS. After adjustment for metabolic syndrome and other cardiovascular risk factors, multivariate logistic regression analysis showed that odds ratios (OR) for CHD, stroke, and CVD in those in the fourth quartiles were 2.34 (95% confidence interval [CI] 1.73 to 3.45), 2.18 (95% CI 1.86 to 3.28), and 2.16 (95% CI 1.80 to 3.29), respectively, compared with those in the first quartile of UA. CONCLUSIONS: Elevated serum uric acid level was associated with CVD, independent of conventional cardiovascular disease risk factors and metabolic syndrome.